Sistem Pengelolaan dan Pengembangan Wakaf Secara Produktif di Pondok Pesantren Al-Uswah Kuala Kabupaten Langkat Menurut Undang-undang No. 41 Tahun 2004 Tentang Wakaf - Siregar, Rosidah; Iqbal, Muhammad Nur; Rangkuti, Ahmad Zuhri (ManBiz: Journal of Management and Business, 2024)
The purpose of this study was to determine the productive waqf management and development system at the Al-Uswah Kuala Islamic Boarding School, Langkat Regency, and also to find out the forms of productive waqf management and development at the Al-Uswah Kuala Islamic Boarding School, Langkat Regency. This type of research includes empirical research with a qualitative approach. The subject of this study involved the Chairperson of the Al-Uswah Kuala Islamic Boarding School Foundation, Nazhir Waqf, and the Community, with a qualitative descriptive research analysis. The results of the research conducted show that the waqf management and development system productively at the Al-Uswah Kuala Islamic Boarding School, Langkat Regency is carried out by administering and collecting data on waqf assets, then recording them in a notarial deed so that they have permanent legal force, and carrying out maximum supervision so that the utilization Waqf assets are in accordance with their function and main objective, which is to develop Islamic education as a place to nurture true Muslims. Then, the productive management and development of waqf at the Al-Uswah Kuala Islamic Boarding School in Langkat Regency is carried out in two forms, namely the physical form in which waqf assets are developed by adding and constructing various buildings needed in the educational process at the institution. Apart from that, it is also being developed in the form of waqf management policies especially for the needs of the students, for example providing free tuition fees for orphans and high achieving students so as to help the Muslim community (santri's parents). While the form of waqf assets is distributed to the surrounding community in the form of donations such as groceries and so on at certain moments. So that the productive management and development of waqf assets is in accordance with Law no. 41 of 2004 concerning Waqf.